Image_1_Is Oligotrophy an Equalizing Factor Driving Microplankton Species Functional Diversity Within Agulhas Rings?.JPEG - Caio Cesar-Ribeiro; Fernanda R. Piedras; Leticia C. da Cunha; Domênica T. de Lima; Luana Q. Pinho; Gleyci A. O. Moser (2020)
From the southwestern termination of the Agulhas current, anticyclonic eddies are emitted and drift across the South Atlantic Ocean. This study is based on a FORSA (Following Ocean Rings in the South Atlantic) oceanographic cruise, from Cape Town (South AFRica) to Arraial do Cabo (Brazil) in June 2015, during which three eddies of different ages (E1, 7 months; E3, 11 months; E5, 24 months) from the Agulhas current were sampled for microplankton identification and determination of functional traits. The stations where sampling occurred at each eddy included a control outside the eddy and three stations inside the eddy—border, midway (between the border and center), and center (identified through satellite images of sea level anomaly—SLA). Functional traits were determined based on microscopic observations and consultation of the literature. An evident decay in the Agulhas eddies toward the west was observed, and each eddy proved to be different. E1 represented a younger and more robust structure. At the same time, the other eddies, E3 and E5, were more alike with similar physical, chemical, and ecological characteristics and almost the same indices values of functional diversity, demonstrating that although their species compositions were different, the strategies used by the species were the same. The most crucial ecological trait for microplankton was nutrition mode. The microplankton contained mainly mixotrophic dinoflagellates and cyanobacteria adapted to oligotrophic conditions. The functional strategy of microplankton did not differ among the eddies and stations, with mixotrophy being the most striking trait. Therefore, the older eddies’ microplankton community fits the neutrality theory, whereby species perform similar ecological functions, and the younger eddy fits in the niche complementarity. Even with the species composition being different in each eddy and/or within the same eddy, the functional strategy was the same, with scarce resources and species selected that best use any source of nutrients or ...